Analysis of Road Traffic Safety through Direct Relative Indicators for Traffic Accidents Fatality: Case of Republic of Macedonia - Babanoski, Kire; Ilijevski, Ice; Dimovski, Zlate (Promet - Traffic&Transportation, 2016)
In the absence of a detailed profile and assessment of the road traffic safety situation in the Republic of Macedonia, the paper will show the analysis by calculating and comparing the direct relative indicators for deaths from traffic accidents in relation to the total population (public risk), the total number of vehicles (traffic risk) and the total number of passenger-kilometres (dynamic traffic risk). Their established trends in the period 2005-2014 will also be shown and then compared with the levels in other European countries. Within the risks, there is additionally the risk of suffering that takes into account the consequences of accidents to people (human losses, heavy and light bodily injuries), which will be calculated and analysed for the area covered by the eight Sectors for Internal Affairs (SIA) in the Republic of Macedonia. For this purpose maps of the public risk of suffering from accidents on the roads will be made, which will closely show the traffic safety situation in the country. The diagnosing of the traffic safety situation will contribute to the creation of new measures and activities or improving the existing ones by the competent authorities in order to promote the road traffic safety.